(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2012)
The aim of the study was to investigate the effect of an ethanol extract of leaf (EEL) of Syzygium cumini against Vibrio cholerae serogroups Ogawa and Inaba. The antimicrobial activity of EEL was evaluated by the disc diffusion method against multi-drug resistant Ogawa and Inaba. The EEL effectively inhibited the growth of both serogroups. This growth inhibition was accompanied by fragmentation of genomic DNA as revealed by agarose gel electrophoresis. This result suggested that the EEL might inhibit bacterial growth involving DNA damage either through activation of signal transduction pathways or through direct interaction of the metabolites present in the EEL with DNA. Therefore, EEL of S. cumini has potential growth inhibitory activity against multi drug resistant Vibrios. This inhibitory effect of EEL might be explored to develop effective candidate(s) to combat cholera. DOI: http://dx.doi.org/10.3329/dujps.v11i1.12483 Dhaka Univ. J. Pharm. Sci. 11(1): 25-28, 2012 (June)